Current approaches to defining the concept of "cross-curricular" - Тверезовська, Н. Т.; Сидорко, В. П. (Pedagogy of Higher and Secondary Education, 2012)
Tverezovsʹka N. T., Sydorko V. P. Current approaches to defining the concept of "cross-curricular". From a philosophical, psychological, pedagogical, methodological, anatomical and physiological, economic, ethnological point of view an attempt to summarize the genesis of the modern definition of the term «interdisciplinary communication».